2021
DOI: 10.1007/s10393-021-01517-z
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and Water-Related Disease Risk in Coastal Bangladesh

Abstract: An increase in surface and ground-water salinity due to climate change is reported to have become a great threat to the health of coastal inhabitants in Bangladesh. However, little is known about how much such salinity affects the risk of water-related diseases and how such risk can be mitigated in the field. This research examines the association between water-related diseases and coastal salinity along with sociodemographic and anthropometric factors. We conduct questionnaire surveys with 527 households: 273… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The study sites are the Khulna and Satkhira districts of the Ganges Brahmaputra Meghna delta region of Bangladesh (Figure 1) where children are highly vulnerable to undernutrition and micronutrient deficiencies as deltaic livelihoods are affected by environmental and climate changes (33), including frequent exposure to floods that cause outbreaks of infectious diseases (34)(35)(36). Compared to major cities in Bangladesh, the population density of both districts is low.…”
Section: Research Contextmentioning
confidence: 99%
“…The study sites are the Khulna and Satkhira districts of the Ganges Brahmaputra Meghna delta region of Bangladesh (Figure 1) where children are highly vulnerable to undernutrition and micronutrient deficiencies as deltaic livelihoods are affected by environmental and climate changes (33), including frequent exposure to floods that cause outbreaks of infectious diseases (34)(35)(36). Compared to major cities in Bangladesh, the population density of both districts is low.…”
Section: Research Contextmentioning
confidence: 99%
“…Due to its extensive low-lying coastal region and frequent exposure to tropical storms, Bangladesh is highly vulnerable to the ingress of saltwater [19] and sea level rise [24] . Saltwater intrusion has detrimental effects on terrestrial environments, increasing salinity levels in both soil and surface water [46] .…”
Section: Water Salinitymentioning
confidence: 99%
“…Our study received ethical approval from the Review Board of the Center for Coastal Development (CCD), with the reference number CCD/extRes/2022/11 (19). We strictly followed the ethical guidelines set forth in the World Medical Association Declaration of Helsinki regarding the inclusion of human subjects.…”
Section: Authors' Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2011) documented drinking water salinity as one of the determinants of infant mortality in coastal Bangladesh. Numerous studies also reported salinity and bacterial contamination with higher incidences of water-borne illnesses including diarrhea, dysentery, cholera, jaundice in coastal Bangladesh ( Asma and Kotani, 2021 ; Hossain et al., 2021 ; Rahman et al., 2017 ; Islam et al., 2011 ). More recently, Akter (2019) argued that drinking water salinity decreases the children’s grade advancement likelihood.…”
Section: Introductionmentioning
confidence: 99%